2017
DOI: 10.4172/2161-1122.1000430
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Based Oral Health Education Program on the Level of Oral Health Knowledge Among Public Intermediate School Girls at Riyadh, 2016

Abstract: Objectives: This study was conducted to assess the impact of oral health education program on the level of oral health knowledge among female public intermediate school students in Riyadh. As well as to evaluate the correlation between their oral health knowledge and selected socio-demographic variables. Methods:A pre-posttest quantitative study was conducted at public intermediate girls' schools in Riyadh. A sample of schools was selected using stratified random sampling technique to reflect the spectrum of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…Studies comparing the effects of various methods of school dental health education programs in this province are very limited; this is the reason that provision of health promotion in public health programs is diminished. 12,13 In our study, a positive change was found in the participants at three months post-intervention period regarding oral health knowledge attitude and practices, and the same result was found with the plaque and gingival Index scores. In addition, the difference in plaque and gingival scores were found more in the Audiovisual-Group than in the Verbal-Group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies comparing the effects of various methods of school dental health education programs in this province are very limited; this is the reason that provision of health promotion in public health programs is diminished. 12,13 In our study, a positive change was found in the participants at three months post-intervention period regarding oral health knowledge attitude and practices, and the same result was found with the plaque and gingival Index scores. In addition, the difference in plaque and gingival scores were found more in the Audiovisual-Group than in the Verbal-Group.…”
Section: Discussionsupporting
confidence: 80%
“…After filling out the questionnaires plaque score was recorded using Sillness and Loe plaque Index, and the gingival score was recorded using Loe and Silness gingival index. 12 Next, the principal investigators did a clinical examination. Finally, students were made to sit in a chair comfortably, and plaque and gingival scores were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[12] Pendidikan kesehatan gigi dan mulut bertujuan untuk mempromosikan kesehatan melalui sarana pendidikan untuk meningkatkan pengetahuan kesehatan mulut untuk adopsi gaya hidup yang lebih sehat, mengubah sikap serta perilaku yang diinginkan. [13] Pendidikan dan promosi kesehatan mulut dapat disampaikan di beberapa forum yaitu rumah sakit, pusat perawatan kesehatan primer, klinik gigi swasta dan sekolah. [14] Beberapa penelitian telah melaporkan hasil positif dari pemberian pendidikan kesehatan antara lain dalam hal kebersihan mulut, perubahan signifikan dalam perilaku menjaga kesehatan mulut, keterampilan menyikat gigi, pengendalian karies, skor plak dan gingivitis.…”
unclassified